Analysis of changes in the area and density of mangroves along the coast of tanjung jabung barat regency from 2015 to 2024 using landsat 8 satellite imagery - Septy Heltria; Ester Restiana Endang Gelis; Farhan Ramdhani; Muhammad Hafidz Ibnu Khaldun; Hamzah Hamzah (Jurnal Perikanan Terpadu, 2026)
Mangrove ecosystems in the coastal area of West Tanjung Jabung Regency are under increasing pressure from anthropogenic activities, highlighting the need for continuous monitoring of changes in their spatial extent and density. This study aims to analyze the changes in the area and density of mangrove ecosystems along the coastal region of Tanjung Jabung Barat Regency during the period 2015–2024 using Landsat 8 OLI satellite imagery. The data were obtained from the USGS Earth Explorer (path 125, row 61) with cloud cover less than 10%. Image processing involved several stages, including preprocessing, band composition, visual digitization, and supervised classification using ArcGIS 10.8 software. Mangrove vegetation density was analyzed using the NDVI (Normalized Difference Vegetation Index), which was categorized into three density classes: sparse, moderate, and dense. The results showed that the total mangrove area decreased by 14%, from 3,488.78 ha in 2015 to 3,009.98 ha in 2024, representing a reduction of approximately 478.8 ha. The most significant decreases occurred in Sinar Kalimantan Village (172.82 ha) and Sungai Dualap Village (42%), while a slight increase was observed in Pangkal Duri Ilir Village (1%). The NDVI-based density analysis indicated that dense mangrove areas increased substantially in Muara Seberang Village by 377.54 ha, whereas the largest decline occurred in Sinar Kalimantan Village by 78.72 ha. Overall, the findings reveal a trend of mangrove degradation mainly driven by land conversion and anthropogenic activities, alongside localized improvements likely due to rehabilitation efforts. These results provide valuable insights for sustainable management and conservation planning of mangrove ecosystems in the coastal zone of Tanjung Jabung Barat Regency